Modelling the Effect of Population Ageing on Government Social Expenditures - John Bryant (New Zealand Government, The Treasury, 2003)
This paper reviews and extends a new framework, developed by Razin, Sadka, and Swagel, for capturing the effect of population ageing on public support for government social expenditures. Razin et al construct up an overlapping generations, median voter model, and investigate the empirical applicability of the model using panel data from 13 OECD countries. Their results suggest that population ageing will put downward pressure on per capita expenditures. These results rest, however, on an assumption that there is only one dependant age group: the old. This paper investigates the consequences of allowing for two such age groups: the young and the old. A replication of Razin et al's empirical analysis, using two dependent age groups rather than one, suggests that population ageing will instead put upward pressure on per capita expenditures. Although these results are tentative, they illustrate the usefulness of including both youth dependency and old-age dependency in Razin et al's framework.
Keywords: D72; E62; J11; 330; Social expenditures; Median voter models; Population Ageing